(untitled) (Revista Sistemas de Producción Agroecológicos, 2010)
The work is part of a project being done CORMACARENA, since 2000, promoting research and the use of alternatives to ensure the rational, equitable and sustainable use of renewable natural resources in their jurisdiction. The activities took place in the towns of Restrepo and Cumaral. The objective was to evaluate the species agronomically CORMACARENA established by five (5) fodder banks in cattle farms and the towns of Restrepo and Cumaral (Meta). Also provide professional technical assistance to five (5) producers implemented fodder banks. The experience gained in recent years at the farm level, farmers with small entrepreneurs, indicates that this being an important technological proposal, the successful implementation and sustainable use of fodder bank mainly depend on the discipline in compliance with the technical recommendations of training opportunities to producers in handling specific bank issues , knowledge of each of the component species and the initiative to adopt the producer by production system and resource availability. Besides the active participation of producers allowed to identify ways of cultivation and use of native species in the region. Therefore, the adoption of these species in the foothills of the Eastern Plains of Colombia should be an ongoing process that must be led by trained extension technicians national institutions for this work and enthusiastic producers have recognized the benefit of these legumes in their farms.